THE COVID-19 HEALTH CRISIS AND CORPORATE DEBT: WHAT IMPACT OF THE CRISIS ON SOME TUNISIAN SMES - Kraima, Mohamed Taher; Boudabbous, Sami (APPS Publications, 2022)
Small and medium-sized enterprises have a key role in economic development and job creation, but lately, and in the footprint of the COVID-19 pandemic, a violent health and economic crisis is emerging that threatens many affected countries.The objective of this study is to assess the effect of the COVID-19 health crisis on the indebtedness of Tunisian SMEs. For this purpose, a sample of 140 SMEs was selected, and for the data analysis, we resorted to the truncated regression methodology via the STATA 12 software, the results show a positive effect of indebtedness on the health crisis of the COVID-19, SMEs are struggling to repay their debts, but there is a delay in repaying them on time. Moreover, the results show precisely that the health crisis of COVID-19 has been the cause of other challenges that prevent SMEs from functioning, which implies the usefulness of the intervention of governments and partners in order to overcome the cash flow difficulties.